Dnmt3b Methylates DNA by a Noncooperative Mechanism, and Its Activity Is Unaffected by Manipulations at the Predicted Dimer Interface - Norvil, Allison B. (Biochemistry, 2016)
The catalytic domains of the de novo DNA methyltransferases Dnmt3a-C and Dnmt3b-C are highly homologous. However, their unique biochemical properties could potentially contribute to differences in the substrate preferences or biological functions of these enzymes. Dnmt3a-C forms tetramers through interactions at the dimer interface, which also promote multimerization on DNA and cooperativity. Similar to the case for processive enzymes, cooperativity allows Dnmt3a-C to methylate multiple sites on the same DNA molecule; however, it is unclear whether Dnmt3b-C methylates DNA by a cooperative or processive mechanism. The importance of the tetramer structure and cooperative mechanism is emphasized by the observation that the R882H mutation in the dimer interface of DNMT3A is highly prevalent in acute myeloid leukemia and leads to a substantial loss of its activity. Under conditions that distinguish between cooperativity and processivity, we show that in contrast to that of Dnmt3a-C, the activity of Dnmt3b-C is not cooperative and confirm the processivity of Dnmt3b-C and the full length Dnmt3b enzyme. Whereas the R878H mutation (mouse homologue of R882H) led to the loss of cooperativity of Dnmt3a-C, the activity and processivity of the analogous Dnmt3b-C R829H variant were comparable to those of the wild-type enzyme. Additionally, buffer acidification that attenuates the dimer interface interactions of Dnmt3a-C had no effect on Dnmt3b-C activity. Taken together, these results demonstrate an important mechanistic difference between Dnmt3b and Dnmt3a and suggest that interactions at the dimer interface may play a limited role in regulating Dnmt3b-C activity. These new insights have potential implications for the distinct biological roles of Dnmt3a and Dnmt3b.